2y-x-2=0

Simple and best practice solution for 2y-x-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-x-2=0 equation:


Simplifying
2y + -1x + -2 = 0
Reorder the terms:
-2 + -1x + 2y = 0
Solving
-2 + -1x + 2y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + -1x + 2 + 2y = 0 + 2
Reorder the terms:
-2 + 2 + -1x + 2y = 0 + 2
Combine like terms: -2 + 2 = 0
0 + -1x + 2y = 0 + 2
-1x + 2y = 0 + 2
Combine like terms: 0 + 2 = 2
-1x + 2y = 2
Add '-2y' to each side of the equation.
-1x + 2y + -2y = 2 + -2y
Combine like terms: 2y + -2y = 0
-1x + 0 = 2 + -2y
-1x = 2 + -2y
Divide each side by '-1'.
x = -2 + 2y
Simplifying
x = -2 + 2y

You can always share this solution

See similar equations:

| 5x+23=2x+107 | | 8-x=2x-10 | | .5(2x-4)=4.8 | | 5(x-1)=(x-3) | | (3y+6)=(4y+7) | | -17=2b-b-10 | | 7[3x-2]+5=6[2x-1]+24 | | 8-x-x=-2 | | -y+2x=4 | | 25=65-2x | | 254-5x=40x+19 | | X+x=2y | | 796-2a=59-3a+1 | | -34+3x=11 | | 4=0.2x-10+0.5x | | 0=2x^3 | | -5r^9+20r^7b^4=0 | | 3x-2(x-1)=9x+4 | | 25m^4-41m^2+16=0 | | 2x-1+(x+5)+x=180 | | .75w+8=.33-7 | | 2x+5=1oy | | 45+33-7= | | -x+19=18 | | 5-4(x+4)=6x-11 | | .028x+3=.035x | | (k+6)(3k+7)=0 | | .028x+3=.035 | | 12+6(1)-9=(2+16)-4(1)-5 | | 6m+3n-3m= | | 3x-10*x=90 | | 20x+40x+80x= | | 4a+3b=24 | | 14-12x+39x=256-60x-657x | | 7(x-1)+8=5(7-x)+12 | | 30x-6=28x-44 | | 14-12x+39=256-60x-657x | | 5x-4[x+9]=2x-3 | | -9=2n-15 | | 2(-18)(5)= | | (5*-11-3)-(8*-11-6)= | | u^4-20u^2+64=0 | | 13x+2(x+1)=10 | | 482.20=230-0.97x | | X^3+3= | | 4x-(2x+3)(3x-5)=49-(6x-1) | | -10x+3y=21 | | 8q^4-22q^3+12q^2=0 | | 8[y+3]=3[2y+12] | | 3x-5=8+6x | | 0.2x^2+-0.8x+-0.2=0 | | (5.63)(2.42)(0)= | | 2cos^2x-3cosx=2 | | 2(9n+5)=-2 | | 26-8y= | | -c^3+c=0 | | 2.6(m+2)=2(m+2) | | 190-3x=33x+22 | | (5*11-3)-(8*11-6)= | | 12.00=0.78h | | 5-8x=56-29x | | 339+34h=458 | | 2.5(m+2)=2(m+2) | | x^6-x^5-21x^4+45x^3=0 | | 24=23-2y |


Related pages


x3-27 factoredyx5simplify 8x 2298.91666 roman numeralsprime factors of 441graph 4x4x 2y 8 0graph of sin 4xminus fractions calculatorsinkxpx40cos3x sin3x4x y 2 graphhow to write 0.25 as a fraction12.50 x 10square root of 2304roman numerals 6005yz5x-3y 2expand 2x 3y 37x 5 5xstep by step simultaneous equationssimplify 4x 6xx 3 2ywhat is the prime factorization of 43cos 2x 0.5roman numerals mmxii99 prime factorization650-195how to write a prime factorization3x 5y 19derivative of sinx 2100 000 dollars in poundssqrt 1214 5x1 1 6 answercos 4x sin 4x cos2x6000 dollars in poundsstep by step differentiation calculator2sin cos1965 in roman numeralsx 4y 164096 square root3r solutionsderivative caculator1991 roman numeralvv qqroman numeral 1988graph x 3y 3math lcm calculatorgcf of 84prime factorization of 612what is 4.75 as a fraction270-180find the prime factorization of 28calculator percent to fractionroman numerals for 1978greatest common monomial factor calculator77kg lb4x 12xprime factorization of 675sinx cos3xprime factorization 2403 000 dollars in poundsthe lcm calculatorderivative of 3x250-270prime factorization of 1982x 6 2y 3y2sin cosderivative of xe x